INNOVATIONS IN TEACHING: INTEGRATION OF STEAM AND PHYSICAL EDUCATION FOR PRIMARY SCHOOL STUDENTS - Glišović, Gordana J.; Jovanović, Emina P. (Metodička teorija i praksa, 2024)
The paper explores the possibilities of integrating STEAM activities with physical education for students of younger grades of elementary school. The goal of this research is to explore the possibilities of integrating STEAM activities with physical education in the education of younger elementary school students. The focus is on identifying the advantages of this approach, analyzing the challenges we face during implementation, and proposing recommendations for overcoming those challenges. The methods of analysis, synthesis and generalization were used in the research. Different approaches to integrating STEAM activities with physical education for junior elementary school students provide numerous benefits, including improving student health and development, encouraging hands-on experience and creativity through the application of science and math concepts in physical activities, and developing social skills through teamwork. However, we face challenges such as limited time for physical education, the need for careful planning of integration into the existing curriculum, lack of resources and the need to develop new methods of learning assessment. To overcome the challenges of integrating STEAM activities with physical education, careful planning of class schedules to ensure sufficient time for comprehensive activities, as well as provision of additional resources such as teacher training and necessary equipment and materials, is critical. Also, it is important to continuously monitor and adapt the curriculum in order to effectively integrate scientific and mathematical concepts into physical activities, while at the same time preserving the basic elements of physical education.